Legal Risk Assessment in Cross-Border Business Agreements between Regulatory Compliance and Profit Optimization - Nugiantari, Ayu Rosita (Journal of Law, Politic and Humanities, 2025)
This study explores the critical role of legal risk assessment in cross-border business agreements, focusing on the balance between regulatory compliance and profit optimization. Using a qualitative approach and literature study method, this research examines existing theories, regulations, and case studies related to legal risk assessment in international business. It identifies eight key risk criteria—ranging from legal system disharmony to regulatory compliance challenges—that influence legal risk assessments in cross-border contracts. The research highlights how differences in legal systems, evolving regulations, and inadequate early-stage risk assessments can create significant risks for companies engaged in international agreements. Furthermore, the study discusses how legal risk assessments can help businesses navigate the tension between compliance with international regulations and the pursuit of profit optimization strategies. By synthesizing insights from academic literature, international legal frameworks, and industry best practices, this study provides a comprehensive framework for integrating legal risk assessments into cross-border business decision-making processes. The findings suggest that companies can achieve sustainable growth by proactively addressing legal risks, ensuring compliance, and optimizing profits in an increasingly complex global business environment. This research contributes to the development of a standardized, adaptive legal risk assessment framework that can be applied across diverse sectors, ensuring both legal integrity and business success.